INTEGRASI DOKTRIN KETERTIBAN UMUM PADA KONTRAK INVESTASI NEGARA INVESTOR GUNA MITIGASI GANTI RUGI LUCRUM CESSANS - A’an Ilham Ardiyansah; Sang Ayu Putu Rahayu; Duhita Driyah Suprapti (Jurnal Padamu Negeri, 2026)
This study analyzes the structural legal dilemma in international investment law caused by the normative rigidity of conventional stability clauses, which triggers a regulatory chill. The central issue examined is the high potential for compensation claims regarding the loss of expected future profits (Lucrum Cessans) filed by investors when host states adjust public policies. The primary objective of this research is to formulate a comprehensive integration model of the public policy doctrine into state-investor investment contracts as an effective limiting instrument against financial claims. Utilizing normative legal research methods through a conceptual approach, this article dissects conflicts between private investor legitimate expectations and a state's sovereign right to regulate. The results indicate that an explicitly integrated public policy clause provides a solid legal basis for state regulatory action. In conclusion, this integration effectively mitigates extensive financial risks from Lucrum Cessans compensation claims while restoring a balanced contractual relationship between host states and foreign investors.